Aerobic granular sludge for high-strength ammonium wastewater treatment: Effect of COD/N ratios, long-term stability and nitrogen removal pathways. (June 2020) - Sarvajith, M.; Kiran Kumar Reddy, G.; Nancharaiah, Y.V.
Graphical abstract: Highlights: Removal of 4000 mg l −1 NH4 + -N was achieved using aerobic granular sludge process. Functional and structural stability of AGS was maintained at low COD/N ratios. Bacterial diversity decreased at higher influent ammonium concentrations. Nitrite oxidizing bacteria washed out at higher NH4 + -N and lower COD/N ratios. Nitritation-anammox was the major nitrogen removal pathway. Abstract: Aerobic granular sludge (AGS) technology is increasingly considered for wastewater treatment. AGS stability particularly under lower COD/N ratios is an impediment for AGS technology. This study evaluated AGS stability and nitrogen removal at different loading rates of 0.03 to 4 kg NH4 + -N m −3 d −1 and COD/N ratios of 18.3 to 0.13. Ammoniacal and total nitrogen removals were high at 99.9% and 99.3%, respectively, during 440 days. MiSeq sequencing revealed a reduction in bacterial diversity and enrichment of ammonia oxidizing bacteria (AOB), anammox and denitrifying bacteria. Quantitative PCR showed enrichment of AOB, anammox bacteria, Nitrospira and denitrifiers. Chemical data and bacterial community supported occurrence of nitritation and anammox pathways. AGS had stable granular structure with excellent settling properties at lower COD/N ≤ 1. Removal of high-strength ammonium could be partly explained by the existing nitrogen pathways suggesting novel mechanisms. Nevertheless, results presented here support implementation of AGS process for ammonium wastewaters.